2019
DOI: 10.3390/en12081432
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Transfer Characteristics of Liquid Sodium in a Solar Receiver Tube with a Nonuniform Heat Flux

Abstract: This paper presents a numerical simulation on the heat transfer of liquid sodium in a solar receiver tube, as the liquid sodium is a promising heat-transfer candidate for the next generation solar-power-tower (SPT) system. A comparison between three mediums—solar salt, Hitec and liquid sodium—is presented under uniform and nonuniform heat-flux configurations. We studied the effects of mass flow rate (Qm), inlet temperature (Tin), and maximum heat flux (qomax), on the average heat-transfer coefficient (h) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…( 19), ( 20), (21), and ( 22) are used to evaluate the physical properties, for Hitec (7% NaNO 3 , 53% KNO 3 , 40% NaNO 2 ) it is obtained from Eqs. (23), ( 24), (25), and (26) [15,39,40,41]. Molten salt is stable as a heat transfer fluid up to temperatures of 595 C, and the temperature at which the decomposition of molten salt starts is between 600 to 700 C. It is challenging to operate a solar receiver with molten salt with a peak heat flux more than 0.8 MW/m 2 .…”
Section: The Effects Of Liquid Sodium and Hitec As Heat Transfer Fluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…( 19), ( 20), (21), and ( 22) are used to evaluate the physical properties, for Hitec (7% NaNO 3 , 53% KNO 3 , 40% NaNO 2 ) it is obtained from Eqs. (23), ( 24), (25), and (26) [15,39,40,41]. Molten salt is stable as a heat transfer fluid up to temperatures of 595 C, and the temperature at which the decomposition of molten salt starts is between 600 to 700 C. It is challenging to operate a solar receiver with molten salt with a peak heat flux more than 0.8 MW/m 2 .…”
Section: The Effects Of Liquid Sodium and Hitec As Heat Transfer Fluidsmentioning
confidence: 99%
“…Messaoud et al [3], utilised helical fins to achieve a better heat transfer from the receiver to the heat transfer fluid, and a receiver with four helical fins was considered the best design. Liu et al [4] developed a numerical model which used four different inserts with non-uniform heat flux. Twisted tapes had the highest Nusselt number and the lowest difference in circumference temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In available design processes [17,34], the fluid temperature and surface temperature of the cavity receiver are normally assumed to be uniform. In a practical cavity receiver, the fluid temperature and surface temperature increases along the flow direction for heat absorption, so the temperature variation should be further considered.…”
Section: Of 19mentioning
confidence: 99%
“…Lu et al [16] further reported the enhanced heat transfer performance of a molten salt receiver with a spirally grooved tube. Liu et al [17] compared the heat-transfer characteristics of solar salt, Hitec and liquid sodium in a solar receiver tube with nonuniform heat flux.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation